Odpowiedzi

2010-04-14T15:18:02+02:00
2 1/3-1 5/6=
7/3 - 11/6=
14/6-11/6=3/6=1/2

-0,18:(0,9)=-0,2

-6,2-(-3,7)=
-6,2+3,7=-2,5

1 8/15 * (-2,4)=
23/15 * -24/10=
46/30 * -72/30=
3314/30=110 4/30



(12.75-3x1/4):(2,2+7 4/5)=
(12,75 -3*0,25):(2,2+7,20)=
(12,75-0,75):9,20=
12,00:9,20=1,30
2010-04-14T15:30:39+02:00
2 1/3-1 5/6=2 2/6 -1 5/6= 1/2
-19:(-0,9)-chyba tak ma byc jak w nawiasie :) =0,2a jak tam nie ma minusa to -0,2
-6,2-(-3,7)= -6,2+3,7= -2,5
1 8/15*(-2 1/25) = 32/15*(-51/25)=1632/375=4 352/375
(12.75-3*1/4):(2,2+7 4/5)=(12,75-3*0,25):(2,2+7,8)=(12.75-0,75):10=
=12:10=1,2
chyba tak :)